Reversible Thermochromism and Strong Ferromagnetism in Two‐Dimensional Hybrid Perovskites. (19th November 2019) - Sun, Bing; Liu, Xiao‐Fei; Li, Xiang‐Yang; Cao, Yang; Yan, Ze; Fu, Lin; Tang, Nujiang; Wang, Qiang; Shao, Xiangfeng; Yang, Dezheng; Zhang, Hao‐Li
Abstract: Two‐dimensional (2D) hybrid perovskites have shown many attractive properties associated with their soft lattices and multiple quantum well structure. Herein, we report the synthesis and characterization of two new multifunctional 2D hybrid perovskites, (PED)CuCl4 and (BED)2 CuCl6, which show reversible thermochromic behavior, dramatic temperature‐dependent conductivity change, and strong ferromagnetism. Upon temperature change, the (PED)CuCl4 and (BED)2 CuCl6 crystals exhibit a reversible color change between yellow and red‐brown. The associated structural changes were monitored by in situ temperature‐dependent powder X‐ray diffraction (PXRD). The (BED)2 CuCl6 exhibits superior thermal stability, with a thermochromic working temperature up to 443 K. The conductivity of (BED)2 CuCl6 changes over six orders of magnitude upon temperature change. The 2D perovskites exhibit ferromagnetic properties with Curie temperatures around 13 K. Abstract : Farbe, Leitfähigkeit, Magnetismus : Zwei neue 2D‐Hybrid‐Perowskite zeigen sowohl Thermochromie als auch Ferromagnetismus. Der (BED)2 CuCl6 ‐Kristall weist eine hohe thermochrome Betriebstemperatur von bis zu 443 K auf, und die dramatische temperaturabhängige Leitfähigkeitsänderung überstreicht sechs Größenordnungen.